(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article explores the multifaceted relationship between demographic changes and the economic activities of selected countries. Specifically, the study analyzes the impact of demographic shifts on labor markets, savings and investment levels, social security systems, and overall economic growth in the United States, Japan, Germany, France, and Uzbekistan. The research examines the challenges and opportunities presented by demographic changes and offers policy recommendations to ensure sustainable economic development.